Encephalitic listeriosis in calves - Santos, Jefferson Andrade dos (2014)
Listeria monocytogenes L. 1/2b was isolated from brains of about one-year-old calves originating from Campos, RJ, Brazil, which exhibited neuro-paralytic symptoms resembling those of rabies. Isolation of the bacteria was realized by using enrichment technique at low temperature and through the biological method. In vivo tests were made with the bacterial culture. The histopathology of the Central Nervous System showed a diffuse inflammatory process of the brain and pia mater with infiltration of monocitary cells and few lymphocytes.